2013
DOI: 10.1007/s10695-013-9861-z
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant status of serum, muscle, intestine and hepatopancreas for fish fed graded levels of biotin

Abstract: Lipid peroxidation, protein oxidation and antioxidant activities of muscle, intestine, hepatopancreas and serum in juvenile Jian carp (Cyprinus carpio var. Jian) were investigated after feeding graded levels of biotin (0.010, 0.028, 0.054, 0.151, 0.330, 1.540 and 2.680 mg kg(-1) diet) for 63 days. Both malondialdehyde and protein carbonyl content in all studied tissues and serum were the lowest in fish fed diets containing 0.151-0.330 mg biotin kg(-1) diet and then increased in fish fed the diet with 2.680 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 63 publications
0
18
0
1
Order By: Relevance
“…Therefore, we surveyed a few serum antioxidant-related parameters, including SOD, CAT, T-AOC, GSH-Px and MDA, to confirm whether COS can improve the antioxidant status of sows. Interestingly, we observed a decreased serum MDA content, which indicates that lipid peroxidation could be reduced by COS (Feng et al 2014). CAT is implicated as an essential defence enzyme against the potential toxicity of hydroxyl radicals, and T-AOC reflects the total antioxidant capacity of the organism (Fang et al 2016;.…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, we surveyed a few serum antioxidant-related parameters, including SOD, CAT, T-AOC, GSH-Px and MDA, to confirm whether COS can improve the antioxidant status of sows. Interestingly, we observed a decreased serum MDA content, which indicates that lipid peroxidation could be reduced by COS (Feng et al 2014). CAT is implicated as an essential defence enzyme against the potential toxicity of hydroxyl radicals, and T-AOC reflects the total antioxidant capacity of the organism (Fang et al 2016;.…”
Section: Discussionmentioning
confidence: 71%
“…Excessive amounts of ROS can lead to lipid peroxidation in organisms. Malondialdehyde (MDA) is the most familiar breakdown product of lipid peroxidation, and its level is frequently used as a direct marker of lipid oxidative damage caused by ROS ( Feng et al., 2014 ). The results of MDA in this study indicated that spermine significantly reduced MDA content in the jejunum, thereby suggesting that spermine could depress lipid peroxidation in weaning rats.…”
Section: Discussionmentioning
confidence: 99%
“…TTFD is a derivative of the B-vitamin thiamine and as such it is a sulfur doi: 10.7243/2054-992X-3-3 containing compound with antioxidant properties [38,39]. Biotin is another B-vitamin which contains sulfur and from animal studies it can also serve as an antioxidant as well [40]. Blood levels of biotin in autism are typically low relative to controls [2].…”
Section: Sulfur Containing Antioxidants As Therapeutics For Autismmentioning
confidence: 99%